The case for localised energy management to support resilient cities - Rodrigues, Lucélia Taranto; Marsh, Julian; Kiamba, Lorna; Gillott, Mark C.; O'Doherty, Travis (2016)
Localised energy generation, ownership and management provide a mechanism to address issues of affordability, energy security, infrastructure resilience and the need to reduce greenhouse gases emissions. There is potential for the growth of community energy schemes in the UK. However, small to medium-sized schemes find it hard to compete with large energy providers. Energy Service Companies (ESCOs) are created to manage the local production and distribution of energy. In Nottingham, the Meadows Ozone Energy Services (MOZES) is a community owned organisation that aims to reduce their carbon footprint, support experimentation and learning in relation to sustainable energy, support energy self sufficiency, help to provide access to affordable energy, and contribute to socio-economic development. In this paper, the authors described some of the benefits that an ESCO can bring to a community drawing on examples from MOZES. The benefits and challenges associated with the implementation of community energy schemes were examined and the results of a questionnaire administered to residents of the Meadows community are presented for the first time. Conclusions are drawn and recommendations are made on how the model developed by MOZES in Nottingham can benefit other communities and contribute to resilient cities for the wider development of distributed energy storage in the UK.